The beneficial effects of menopausal hormone therapy on renal survival in postmenopausal Korean women from a nationwide health survey - Shin Young Ahn (Nature Portfolio, 2021)
Abstract Several studies have demonstrated the nephroprotective effects of estrogen on renal damage. In light of the inconsistent results of previous findings, this study aims to evaluate the in-depth role of menopausal hormone therapy (MHT) on the development of end stage renal disease (ESRD). 3,109,506 Korean adult women who had undergone a medical examination in 2009 (index year) were initially identified for inclusion in this study. We excluded subjects had not experienced menopause naturally, had data missing for at least one variable, and were diagnosed with ESRD within 1 year from the index year. MHT data was obtained from self-reporting questionnaires and the primary outcome was the development of ESRD from the index year until December 31, 2018. A final total of 1,460,311 subjects were included in this study. The participants were divided into four groups according to the duration of MHT; no history of MHT, MHT < 2 years, 2 ≤ MHT < 5 years, MHT ≥ 5 years. During the 9-year study period, a total of 4905 participants developed ESRD. The participants who had a history of MHT use were found to have a 30% reduced risk of developing ESRD. Results from the subgroup analyses were similar to that of the primary study. The findings in this study demonstrate the beneficial effects of MHT on the development of ESRD in postmenopausal women. Based on results, our study may offer suggestions for further studies to investigate the therapeutic options on kidney disease.